A. -1.3
B. 4.5
C. -5.4
D. 3.1
Answer:
(3x+4)(3x+4) is factor of given expression.
B is correct.
Step-by-step explanation:
We are given an expression ![9x^2+24x+16](https://tex.z-dn.net/?f=9x%5E2%2B24x%2B16)
Formula: ![a^2+2ab+b^2=(a+b)^2](https://tex.z-dn.net/?f=a%5E2%2B2ab%2Bb%5E2%3D%28a%2Bb%29%5E2)
First we write each term as perfect square as formula.
![\Rightarrow 9x^2+24x+16](https://tex.z-dn.net/?f=%5CRightarrow%209x%5E2%2B24x%2B16)
![\Rightarrow (3x)^2+2\cdot 3x\cdot 4+4^2](https://tex.z-dn.net/?f=%5CRightarrow%20%283x%29%5E2%2B2%5Ccdot%203x%5Ccdot%204%2B4%5E2)
Using formula , a=3x and b=4
![\therefore (3x)^2+2\cdot 3x\cdot 4+4^2=(3x+4)^2](https://tex.z-dn.net/?f=%5Ctherefore%20%283x%29%5E2%2B2%5Ccdot%203x%5Ccdot%204%2B4%5E2%3D%283x%2B4%29%5E2)
Now we write same number two times.
Hence, (3x+4)(3x+4) is factor of given expression.
A-4b that’s my answer hope this help